Innovation and Practice of Ideological and Political Teaching in Curriculum Driven by Problem Chains with the Support of Rain Classroom - Yuhuan, Li; Xinyuan, Zhang (RIRAI Publisher, 2025)
In the new era, the comprehensive advancement of ideological and political education in curricula must address the issue of the